Thinking photography - Burgin, Victor (New York (N.Y.) : Palgrave Macmillan, 1990)
- The author as producer / Walter Benjamin##- Critique of the image / Umberto Eco##- Photographic practice and art theory / Victor Burgin##- On the invention of photographic meaning / Allan Sekula##- The currency of the photograph / John Tagg##- Looking at photographs / Victor Burgin##- Making strange: the shattered mirror / Simon Watney##- Photography, phantasy, function / Victor Burgin.
Thinking photography brings debates within the theory and practice of communications and culture, in this case in photography and photography criticism
boek